Benign Biliary Strictures - Altman, Ashley; Zangan, Steven M. (Seminars in Interventional Radiology, 2016)
Differentiating benign and malignant biliary strictures is a challenging and important clinical scenario. The typical presentation is indolent and involves elevation of liver enzymes, constitutional symptoms, and obstructive jaundice with or without superimposed or recurrent cholangitis. While overall the most common causes of biliary strictures are malignant, including cholangiocarcinoma and pancreatic adenocarcinoma, benign strictures encompass a wide spectrum of etiologies including iatrogenic, autoimmune, infectious, inflammatory, and congenital. Imaging plays a crucial role in evaluating strictures, characterizing their extent, and providing clues to the ultimate source of biliary obstruction. While ultrasound is a good screening tool for biliary ductal dilatation, it is limited by a poor negative predictive value. Magnetic resonance cholangiopancreatography is more than 95% sensitive and specific for detecting biliary strictures with the benefit of precise anatomic localization. Other commonly employed imaging modalities include endoscopic retrograde cholangiopancreatography with endoscopic ultrasound, contrast-enhanced CT, and cholangiography. First-line treatment of benign biliary strictures is endoscopic dilation and stenting. In patients with anatomy that precludes endoscopic cannulation, percutaneous biliary drain insertion and balloon dilation is preferred.
Keywords: biliary strictures; benign stricture; percutaneous transhepatic cholangiogram; percutaneous biliary drainage; interventional radiology